Coordenadas del imaginario: Protocolo para el uso de las cartografías culturales - Jorge A. González (Estudios sobre las Culturas Contemporáneas)
The author presents the basic elements of a protocol for objectivating the cartographic development of cities over long time periods. Beginning with a brief discussion of the theoiy of fields specialized in meaning production, the manner of making observable the traces of unequal processes in the cultural formation of cities is discussed in a form that is both empirical and historical.